Coordinate regulation of HOX genes in human hematopoietic cells. - Magli, M C (1991)
Hematopoiesis is a continuous process in which precursor cells proliferate and differentiate throughout life. However, the molecular mechanisms that govern this process are not clearly defined. Homeobox-containing genes, encoding DNA-binding homeodomains, are a network of genes highly conserved throughout evolution. They are organized in clusters expressed in the developing embryo with a positional hierarchy. We have analyzed expression of the four human HOX loci in erythroleukemic, promyelocytic, and monocytic cell lines to investigate whether the physical organization of human HOX genes reflects a regulatory hierarchy involved in the differentiation process of hematopoietic cells. Our results demonstrate that cells representing various stages of hematopoietic differentiation display differential patterns of HOX gene expression and that HOX genes are coordinately switched on or off in blocks that may include entire loci. The entire HOX4 locus is silent in all lines analyzed and almost all the HOX2 genes are active in erythroleukemic cells and turned off in myeloid-restricted cells. Our observations provide information about the regulation of HOX genes and suggest that the coordinate regulation of these genes may play an important role in lineage determination during early steps of hematopoiesis.